Effects of achievement goals on perceptions of competence in conditions of unfavourable social comparisons: The mastery goal advantage effect. (11th June 2017) - Kamarova, Sviatlana; Chatzisarantis, Nikos L. D.; Hagger, Martin S.; Lintunen, Taru; Hassandra, Mary; Papaioannou, Athanasios
Abstract : Background: Previous prospective studies have documented that mastery‐approach goals are adaptive because they facilitate less negative psychological responses to unfavourable social comparisons than performance‐approach goals. Aims: This study aimed to confirm this so‐called 'mastery goal advantage' effect experimentally. Methods: A 2 × 3 design was adopted where achievement goals (mastery vs. performance) and normative information (favourable vs. no‐normative information vs. unfavourable) were manipulated as between participant factors. Sample: Participants were 201 undergraduates, 57 males and 144 females, ranging in age from 17 to 55 years ( M age  = 22.53, SD  = 6.51). Results: Regression analyses pointed out that experimentally induced mastery‐approach goals facilitated higher levels of competence and happiness with task performance than experimentally induced performance‐approach goals in conditions of unfavourable social comparisons. In contrast, although performance‐approach goals yielded the highest levels of happiness with task performance in conditions of favourable social comparisons, this positive effect of performance‐approach goals did not extend to perceptions of competence. Conclusion: Current findings broaden understanding of the adaptive nature of mastery‐approach goals and suggest that it is possible to modulate aversive responses to unfavourable social comparisons by focusing attention on mastery‐approach goals.